Attitude of medical students towards the use of audio visual aids during didactic lectures in Pharmacology in Gandhi Medical College, Bhopal, India - Chitapure, Faizan; Hindoliya, Mukesh (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Students favthisteaching methods employing combination of audio visual aids and blackboard teaching over didactic lectures not using these aids. Different methods of lecture are-blackboard teaching, power point presentations (PPT) and mix of aids. This study was primarily done to know the students’ attitude and preferences regarding the lectures using PowerPoint (PPT) presentations and the traditional ‘black-board teaching’ method with an aim to improve the quality of didactic lectures in pharmacology by their appropriate use in further teaching – learning process, with an aim to improve their use in didactic lectures. Methods: A questionnaire-based observational study (annexure-1) observational study was conducted among all the medical students of 4th semester MBBS attending theory classes in the department of Pharmacology in Gandhi Medical College, Bhopal. Results: In this study, as a whole Majority 68 % (42 students) of students preferred mix of aids as teaching method over blackboard and power point. Sixty two students participated in the study out of which 58% (36) were male and students 42% (26) were female. Students told that the lectures using mix of aids were well organized and the lecture contents were well informative. As far as matter of suggestions is concerned 46 (74.2 %) students gave suggestions to improve teaching methods. As compared to blackboard the lectures taken on PowerPoint were clearly visible and well audible to all the students of the classroom.. Conclusions: This study demonstrates that lectures delivered by using a mixture of audio visual aids are more appreciated by the students over blackboard teaching and power-point teaching individually. For further improving their lectures, if possible teachers should plan to implement feasible student suggestions by using a combination of audio visual aids.